Trade unions, political unions and social movement unions: a case study of the National Union of Metalworkers of South Africa (NUMSA) in the context of Polokwane - Anisha, Edwin C. (My University, 2011)
Issues regarding the role of trade unions in the social transformation of nation-states still remain an area of huge debate in academic and official circles - even within trade unions themselves. The debate has centred largely on the capacity and/or appropriateness of political involvement of trade unions. A major concern relates to the temptation for labour to become incorporated in the course of its insertion into politics. Lately, this debate has resonated around developing countries involved in implementing Bretton Woods-inspired reforms, with their stylized economic models that emphasize greater openness to the market; usually at immense social costs and distemper. The challenge appears to be greater in those countries undertaking (concurrently) substantial political and economic reforms in form of institutionalizing democratic governance and marketled economic growth. What has become customary in such countries is massive resentment and opposition towards authorities by subaltern groups led by the working class and their organizations, mainly as a result of deprivations associated with such policies. The consequence has regularly been the recourse to forms of authoritarianism by ruling elites and governments of these countries in order to push through these reforms - regardless of their performance on the ground. The harsh measures associated with these policies, particularly for workers and the poor, has frequently resulted in tensions between organized labour and the state-even in climes that have had a long history of close labour-state relations. More interesting for analysts and observers has been the relative inability for labour to respond to such developments in countries where a corporatist culture has fostered, in spite of the fact that it usually takes the heaviest toll from such policies. This has tended to support the argument that insertion into politics and participation in corporatist arrangements leads to a permanent loss of oppositional skill and more vibrant and militant trade union tradition. The South African case largely adjusts to the picture painted above - at least up till recently. A major change in the leadership of the ANC largely as a result of mobilization of organized labour and its allies has rekindled the debate over the veracity of the narratives that attribute permanence to union political and organizational forms. The view of this research is that these trade union features mutate. The seeming resurgence of the South African trade union as gauged from the Polokwane events has encouraged study on these features. NUMSA was adopted as case study for this research. The research question is quite straight: What is NUMSA’s political orientation and its organizational form, especially in the light of its traditions and developments at Polokwane? Can NUMSA be described as a political union, business union or social movement union? The results of the study reveal a complex picture that shows the presence of elements of all these union types within NUMSA. However, the union continues to show a strong tendency toward independent politics and an organizational form that embodies transformational attributes that are strongly suggestive of the social movement union type